Detrital apatite geochemistry and thermochronology from the Oligocene/Miocene Alpine foreland record the early exhumation of the Tauern Window - Hülscher, Julian; Sobel, Edward R.; Verwater, Vincent; Groß, Philip; Chew, David; Bernhardt, Anne (Basin research, 2021)
The early exhumation history of the Tauern Window in the European Eastern Alps and its surface expression is poorly dated and quantified, partly because thermochronological and provenance information are sparse from the Upper Austrian Northern Alpine Foreland Basin. For the first time, we combine a single-grain double-dating approach (Apatite Fission Track and U-Pb dating) with trace-element geochemistry analysis on the same apatites to reconstruct the provenance and exhumation history of the late Oligocene/early Miocene Eastern Alps. The results from 22 samples from the Chattian to Burdigalian sedimentary infill of the Upper Austrian Northern Alpine Foreland Basin were integrated with a 3D seismic-reflection data set and published stratigraphic reports. Our highly discriminative data set indicates an increasing proportion of apatites (from 6% to 23%) with Sr/Y values <0.1 up-section and an increasing amount of apatites (from 24% to 38%) containing >1,000 ppm light rare-earth elements from Chattian to Burdigalian time. The number of U-Pb ages with acceptable uncertainties increases from 40% to 59% up-section, with mostly late Variscan/Permian ages, while an increasing number of grains (10%-27%) have Eocene or younger apatite fission track cooling ages. The changes in the apatite trace-element geochemistry and U-Pb data mirror increased sediment input from an ≥upper amphibolite-facies metamorphic source of late Variscan/Permian age - probably the Ötztal-Bundschuh nappe system - accompanied by increasing exhumation rates indicated by decreasing apatite fission track lag times. We attribute these changes to the surface response to upright folding and doming in the Penninic units of the future Tauern Window starting at 29-27 Ma. This early period of exhumation (0.3-0.6 mm/a) is triggered by early Adriatic indentation along the Giudicarie Fault System.
Gesehen am 14.12.2021